Dokumen Perencanaan Portfolio Layanan TI Berdasarkan ITIL V3 Untuk Mendukung Keputusan Investasi TI Pada AirNav Indonesia Cabang Surabaya - Rahman, M. Putra Nur; Sutomo, Erwin; Nurcahyawati, Vivine (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2020)
AirNav Indonesia Surabaya Branch, the current condition of IT services used to support business services is not in accordance with IT service requirements, but based on operational needs. From this AirNav Indonesia Surabaya Branch cannot optimize investment and the competitive value of business services. The impact of this problem is that AirNav Indonesia Surabaya Branch cannot know the benefits and feasibility of investing in IT services by measuring acceptable risk. Based on these impacts, it is necessary to make an IT service planning document based on the ITIL Framework Version 3 2011, so that AirNav Indonesia Surabaya Branch provides services that meet the needs of business services and the benefits derived from the services provided. The results of the planning of the IT service portfolio document are the IT services catalog consisting of 2 IT services namely human resource control and e-education which are categorized in the service pipeline, and 3 IT services namely e-flight control, e-IT support airlines, and e-assisstance that are categorized in the service catalog. The results of the initial investment priority analysis of services are e-human resource control with a value of 34.7% ROI as the highest priority, e-IT flight support with an ROI value of 28.06%, e-flight control ROI of 21.02%, e-assisstance ROI 19.51% and electronic education with ROI value of 14.82% as the lowest value.